Quality of life outcomes in patients with breast cancer - Theofilou Paraskevi (Frontiers Media S.A., 2012)
Health-related quality of life is now considered an important endpoint in cancer clinical trials. It has been shown that assessing quality of life in cancer patients could contribute to improved treatment and could even serve as a prognostic factor along with medical parameters. This paper presents a review of quality of life outcomes in patients with breast cancer according to previous descriptive findings. This is a bibliographic review of the literature covering publications that appeared in English language biomedical journals between 1987 and 2008. The search strategy included a combination of the key words quality of life and breast cancer in the titles of published articles. The major findings are summarized and presented under different headings: evaluation of health-related quality of life i) at the time of diagnosis, ii) during treatment, and iii) after the completion of treatment. Breast cancer patients receiving chemotherapy might experience several side-effects and symptoms that have a negative effect on their quality of life. Also adjuvant hormonal therapies were found to have a similar negative impact on quality of life. Psychological distress-anxiety and depression were found to be common among breast cancer patients. Symptoms-pain, fatigue, and insomnia were among the most common symptoms reported. There was quite an extensive body of literature on quality of life in breast cancer patients. These papers have made a considerable contribution to improving breast cancer care.